The Impact of Cell Phone Usage on Fall Risk and Postural Control During Free-Standing - Michalina Gulatowska; Michalina Błażkiewicz (Applied Sciences)
Smartphone use raises concerns about forward head posture, and the high cognitive load and reduced situational awareness involved increase fall risk. This study aimed to assess the impact of smartphone usage (both holding and texting) on fall risk and postural control in healthy young adults. Thirty-three young adults completed three identical 20-s trials in static (AMTI platform) and dynamic (Balance Biodex platform) conditions, including (1) the baseline (eyes open and standing still), (2) passive phone use (holding and looking at the phone with the screen off), and (3) a dual task (texting while standing). Postural control was assessed using linear measures (CoP path length and the Fall Risk Test index) and nonlinear metrics (sample entropy, fractal dimension, and the Lyapunov exponent). The results indicated that smartphone use, especially texting, significantly increased CoP variability in the anteroposterior direction and Fall Risk Test values, highlighting reduced stability. A nonlinear analysis revealed decreased adaptability and the complexity of postural control during phone use. These findings suggest that mobile phone interactions impair balance and increase fall risk due to cognitive and physical distractions.